Evaluatıon Of The Nasal Aırway Followıng Rapıd Maxıllary Expansıon Wıth Computerızed Tomography - Cenk Doruk (Galenos Yayinevi, 2004)
In this study nasal airway changes following rapid maxillary expansion was evaluated with computerized tomography. In the study nasal airway volumes of 10 bilateral maxillary construction cases (6 girls and 4 boys) were measured with computerized tomography before the rapid maxillary expansion. Second measurements were done after the six months retention period. The amount of expansion at the maxilla was found by measuring the inter canine and inter molar width on the dental stone models of patients. The results were assessed by Wilcoxon test. Both inter canine and inter molar width increase were found statistically significant. The nasal airway changes were found statistically significant when the computerized tomography measurements were evaluated.